Recontextualization of Heritage Tourism in Local Cultural Governance - I Komang Surya Artawan; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Bali’s tourism development has historically relied on cultural heritage as a fundamental pillar of destination development and a key driver of regional economic growth. However, the expansion of mass tourism has intensified cultural commodification, which poses significant risks to the sacred values, symbolic meanings, and social legitimacy of indigenous communities as the rightful custodians of cultural heritage. This article aims to analyze the development of heritage tourism in Bali from a Public Administration perspective, particularly within the framework of cultural governance and sustainable tourism policy. This study employs a qualitative approach through a systematic literature review of reputable national and international journals, as well as relevant public policy documents. The analysis is linked to public administration theories, particularly collaborative governance and sustainable public management, to examine the roles of state and non-state actors in cultural tourism governance. The findings indicate that heritage tourism can serve as a strategic public policy instrument for cultural sustainability when it is managed collaboratively, places indigenous communities at the center of decision-making processes, and is supported by regulations that are sensitive to local values such as Tri Hita Karana. Policy implications highlight the need to strengthen local government capacity as facilitator, regulator, and mediator in balancing economic, social, and cultural interests in an equitable manner. Keywords: Bali, Cultural Governance, Heritage Tourism, Public Administration, Sustainable Tourism.